SURVEILLANCE EDUCATION navigating the conspicuous absence of privacy in schools. - Higdon, Nolan, 1983-; Butler, Allison ([S.l.] : ROUTLEDGE, 2024)
Surveillance Education explores the pervasive use of digital surveillance technologies in schools and assesses its pernicious effects on students. Recognizing that the use of digital technologies will persist, the authors instead offer practical ways to ameliorate their impact. In our era of surveillance capitalism, digital media technologies are ever more intertwined into the educational process. Schools are presented with digital technologies as tools of convenience for gathering and grading student work, as tools of support to foster a more equitable learning environment, and as tools of safety for predicting or preventing violence or monitoring mental, emotional, and physical health. Despite a dearth of evidence to confirm their effectiveness, digital data collection and tracking is often presented as a way to improve educational outcomes and safety. This book challenges these fallacious assumptions and argues that the use of digital media technologies has caused great harm to students by subjecting them to oppressive levels of surveillance, impinging upon their right to privacy, and harvesting their personal data on behalf of Big-Tech. In doing so, the authors draw upon interviews from K-12 and higher education students, teachers, and staff, civil rights and technology lawyers, and educational technological programmers. The authors also provide practical guidance for teachers, administrators, students, and their families seeking to identify and combat surveillance in education. This urgent, eye-opening book will be of interest to students and educators with interests in critical media literacy and pedagogy and the sociology of technology and education.
Keywords: Electronic surveillance; Privacy; Students; EDUCATION / Educational Policy & Reform / General; EDUCATION / Philosophy & Social Aspects; EDUCATION / Classroom Management